A comparison of the physical fitness of individuals with intellectually disabilities autism spectrum disorders and Down syndrome diagnosis - Yılmaz, Atike; Mirze, Fatih (Taylor & Francis Ltd, 2022)
Introduction: This article reports the physical abilities and physical wellness of three groups of children with different neurodevelopmental disabilities: Autism, Down Syndrome and Intellectual Disability. Methods: The causal-comparative research method was implemented in this study. The participants comprised 32 students with moderate intellectual disabilities, 18 with autism spectrum disorder, and 22 with down syndrome. The body mass index (BMI), flexibility, standing long jump, sitting height, stroke length, and medicine ball throwing levels were measured for physical fitness, and the groups were compared afterward. The Kruskal Wallis-H Test and Mann-Whitney U Test were applied to determine the differences between the groups' physical fitness averages for the statistical analysis. Results: Statistically significant differences were obtained in BMI, standing long jump, stroke length, and medicine ball throwing variables (p < 0.05). However, no statistically significant difference was discovered for the flexibility and sitting height variables (p > 0.05). The BMI, sitting height, and stroke length levels for the group with autism spectrum disorder were higher than the other groups, as the flexibility levels of the group with down syndrome were higher than the other groups. Students with intellectual disabilities were demonstrated to have better values than other groups regarding standing long jump and medicine ball throwing performances. Conclusions: Objective information about the physical fitness of individuals with children with different neurodevelopmental disabilities was obtained. In addition, the data obtained with these children will contribute to future plans for movement training as well as the content and frequency of the interventions, and will guide the development of new strategies to develop physical abilities and physical wellness.
Keywords: physical fitness; autism spectrum disorder; down syndrome; intellectual disability; moderate disability; Bone-Mineral Density; Mental-Retardation; Motor Proficiency; Children; Health; Adolescents; Adults; Youth; Exercise; People